PERAN KESADARAN KESEHATAN DAN PERHATIAN PADA KEAMANAN MAKANAN TERHADAP SIKAP DAN MINAT KONSUMEN DALAM MEMBELI MAKANAN ORGANIK - Kutresnaningdian, Firdha; Albari, Albari (Jurnal Ilmu Manajemen, 2012)
This study related with the attitudes and purchases intention as a form of disclosure consumer needs and wants. This study, important issues about health consciousness and food safety concerns associated with organic food. Linkage the four variables in a research model of health consciousness and food safety concerns as exogenous, consumer attitudes as an intervening/mediator variable, and the consumers intention to buy organic food as an endogenous variable. Sample as many as 96 people, selected by convenience sampling and involve potential consumers who have never bought or certain dishes made from organic foods. Data were analyzed with regression analysis and the data processing program SPSS version 17.0 was able to prove that the consumer attitude as an intervening variable purely for health consciousness and consumers intention. While the food safety concerns can be a positive influence, directly or indirectly (through attitude) to the consumers intention to buy organic food.